How do universities communicate on Tik Tok? - Sidorenko Bautista, Pavel; Cabrera Méndez, Margarita; Torrente-Martínez, María-Jesús (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
To determine how universities worldwide use TikTok, 7,880 TikTok posts from 118 institutional university profiles were reviewed and categorized through a systematic review. The results show an initial effort by universities to search for institutional content, although from 2021 onwards an increase in playful content focused on the university community is reported, making evident the need to exploit the platform with the corresponding narrative style, aesthetics, and particular times, thus connecting more efficiently with its target audience and betting on consolidating this community both in the real and digital terrain.